2015
DOI: 10.17221/8458-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-induced hypophagia is mediated by 5-HT<sub>2</sub>c receptors in neonatal layer-type chicken

Abstract: Opioidergic and serotonergic (5-HTergic) systems have crucial role in central regulation of food intake. This study was designed to investigate the role of the opioidergic system and the interaction with the 5-HTergic system in opioid-induced feeding behaviour in 3-h food-deprived (FD 3 ) neonatal layer-type chicks. In total 432 chickens were allocated into 9 experiments, each per 4 treatment groups. In Experiment 1, birds were intracerebroventricularly (ICV) injected with D-Ala2-NMe-Phe4-Glyol5-enkephalin (DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Central mechanisms for appetite regulation in chicken are somewhat dissimilar from those in mammals. It is reported that ICV injection of DAMGO (125,250, and 500 pmol) inhibited while DPDPE (20, 40, and 80 nmol) and U-50488H (10, 20, and 40 nmol) increased food intake in layer-type chicken (Shojaei et al 2015). However, μ-, δ-, and κ-opioid receptors are known as an orexigenic neurotransmitters (Kaneko et al 2012;Kozlov et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Central mechanisms for appetite regulation in chicken are somewhat dissimilar from those in mammals. It is reported that ICV injection of DAMGO (125,250, and 500 pmol) inhibited while DPDPE (20, 40, and 80 nmol) and U-50488H (10, 20, and 40 nmol) increased food intake in layer-type chicken (Shojaei et al 2015). However, μ-, δ-, and κ-opioid receptors are known as an orexigenic neurotransmitters (Kaneko et al 2012;Kozlov et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The intracerebroventricular (ICV) injection of μ-and δ-opioid receptor agonists exerts orexigenic effects in mammals (Kaneko et al 2012). The ICV injection of μ-opioid receptor agonist decreases while that of δ-and κ-opioid receptor agonists increases food intake in neonatal meat-type (Shiraishi et al 2008) and layer-type chicken (Shojaei et al 2015).…”
Section: Doi: 1017221/2/2016-cjasmentioning
confidence: 99%
“…The µ receptor of opioid declines food consumption in chicken; however, other receptors enhance food desire (Zendehdel et al 2016). There are some interactions between opioids and other brain mediators such as 5-HT (Shojaei et al 2015), histamine (Jaefari et al 2018), NE (Nayebzadeh et al 2020), CBs (Zendehdel et al 2015c), glutamate (Torkzaban et al 2018), nitric oxide (NO) (Alimohammadi et al 2015), and OT (Raji-Dahmardeh); given this, the reduction effect of DAMGO (µ-opioid receptor agonist) is amplified by CB 1 and CB 2 receptors antagonist, H 3 receptor antagonist, and L-arginine (the precursor of NO) whereas that is diminished by NMDA and mGlu1 receptors antagonist, OT antagonist, β 2 receptor antagonist, H 1 receptors antagonist, and 5-HT 2c receptor antagonist. Also, DPDPE (δ-opioid receptors agonist) induced hyperphagia is decreased by α 1 receptor antagonist, while that is increased by AMPA glutamate receptors antagonist.…”
Section: Opioidsmentioning
confidence: 99%
“…Each bird was injected once only. These doses of drugs were calculated based on the previous studies (Bungo et al, 2004(Bungo et al, , 2005Taati et al, 2009;Shojaei et al, 2015;Zendehdel et al, 2015Zendehdel et al, , 2016a and our pilot studies (un-published data). Right away after the injection, chickens were returned to their individual cages and provided ad libitum food (pre-weighed) and water.…”
Section: Feeding Experimentsmentioning
confidence: 99%
“…The intracerebroventricular (ICV) injection of [D-Ala 2 , NMe-Phe 4 , Gly 5 -ol]-enkephalin (DAMGO) and β-casomorphin (µ-opioid receptor agonists) induce hypophagia while [D-Pen 2, 5 ]-enkephalin (DPDPE) (δ-opioid receptor agonist) exerts orexigenic effects in mammals (Kaneko et al, 2012). The ICV injection of µ-opioid receptor agonists induces hypophagia while δ-opioid receptor agonist and U-50488H (κ-opioid receptor agonist) has a hyperphagic effect in neonatal layer and broiler chicks (Bungo et al, 2004;Shiraishi et al, 2008, Shojaei et al, 2015Zendehdel et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%